Solving the machine set-up problem:a case with a university production workshop. (2009)
This paper defined and solved the machine set-up problem as a combinattorial optimization problem. Based on this, a PC based software for solving the machine set-up problem was developed and adapted for an easy-to learn-apply in a University Production Engineering workshop situation. The system stores pertient data and has features for determining the optimal sequence of production and relevant information for operator's quick manual setting-up of machine. This approach to managing the workshop was compared to the exisitng approach of selecting parts randomly. The innovation was found to improve perfomance between 23 to 55%.